Culture of Nursing Care in Iranian Nursing Homes: An Ethnographic Study - Batool Pouraboli; Zahra Sarkoohi; Nahid Dehghannayeri; Sedigheh Khodabandeh Shahraki (Kerman University of Medical Sciences, 2024)
Background: The aging of the population and an increase in the number of older adults require long-term care and a greater number of nursing homes (NHs). Consequently, identifying relevant cultural factors in NHs may contribute to meeting care needs. This study aimed to explore the culture of nursing care for older adults in NHs in Iran.Methods: This interpretive ethnographic study was conducted in two NHs in Kerman. The data were collected through fieldwork, participant observations, field notes, and semi-structured in-depth interviews with 26 staff and 7 residents. The collected data were analyzed through content analysis.Results: The culture of care in NHs revolves around 3 themes including "task-oriented care", "care deficiency", and "enthusiastic care".Conclusion: The results emphasized the value of the cultural atmosphere embedded in NHs. The provided care mostly met the physical and immediate needs of older adults (task-oriented care). In addition, establishing an emotional relationship with older adults can help them better accept care and reduce illness and disability in them.